If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (64x + 67y) + (-10x + 39y) = 0 Remove parenthesis around (64x + 67y) 64x + 67y + (-10x + 39y) = 0 Remove parenthesis around (-10x + 39y) 64x + 67y + -10x + 39y = 0 Reorder the terms: 64x + -10x + 67y + 39y = 0 Combine like terms: 64x + -10x = 54x 54x + 67y + 39y = 0 Combine like terms: 67y + 39y = 106y 54x + 106y = 0 Solving 54x + 106y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-106y' to each side of the equation. 54x + 106y + -106y = 0 + -106y Combine like terms: 106y + -106y = 0 54x + 0 = 0 + -106y 54x = 0 + -106y Remove the zero: 54x = -106y Divide each side by '54'. x = -1.962962963y Simplifying x = -1.962962963y
| -3z-(-8)=-16 | | (79x-67y)-(51x+37y)= | | 3p-3p+2p+3=17 | | 6(p+3)-2(p-1)=16 | | 2(-3x+1)=4(x-2) | | 4(j+-1)=-16 | | (10x+2y)(4x-11y)= | | -2(5x+12)-5=6(3X-2)-10 | | t/9=-28 | | 13x+1=-13+27 | | (63x+50y)-(19x-17y)= | | (2-z)(4z+5)=0 | | -10+(-2)=-6x | | 2(w-13)=12 | | 3(j-20)=-3 | | 15x-17=3+10x | | 1-3n=16-6n | | 15x^2y+8xy^2+y^3=0 | | (6p+7q)(-2p+10q)= | | 8n^2-18N-5=0 | | 3(C-D)D= | | p^2-15p+50=0 | | (4u+9)(1-u)=0 | | 7/8a-5/3a | | 8n-(5n+4)=17 | | x^1/2=13 | | (4u+9)(1-0)=0 | | 5y-3y+7=4y+7-2y | | 6y+2y=26 | | -3(4b-10)=12(24+60) | | sqrt(x)=13 | | 3(x+2)+2(x+4)=-1 |